Measuring impacts and informing modelling processes - Trewartha, G.; Preatoni, E.; Cazzola, D. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Primarily using rugby union situations as case study examples for the practical demonstration, the initial part of the session will discuss both familiar and emerging techniques to measure the biomechanics of sport impact situations. We will cover some of the issues that need to be accounted for to acquire robust data in such complex environments, and we will discuss how experimental measures can be either used in their own right to develop knowledge of impact biomechanics or can provide data to input a modelling pipeline and for model validation purposes.